Compliant control of electric power assisted steering systems in vehicles - Çetin, Ahmet Emre (My University, 2009)
TAŞITLARDA ELEKTRİK GÜCÜ DESTEKLİ DİREKSİYON SİSTEMLERİNİN UYUMLU KONTROLÜ Bu çalışmada empedans ve sertlik kontrol stratejilerini elektrik gücü destekli direksiyon sistemlerine uygulayarak test etmek amacı ile sürücü etkileşim (direksiyon) ve araç yönlendirme (direksiyon kutusu) kablolu sürüş test düzenekleri inşa edildi. Geliştirilen kontrolcüleri test edebilmek için doğrusal olmayan 4 serbestlik dereceli bir araç modeli oluşturuldu. Bu model doğrusal, yanal, savrulma ve yarı-statik yalpalama dinamiklerini içermektedir. Araca tekerlek-yol etkileşiminden gelen kuvvetleri hesaplayabilmek için Dugof tekerlek modeli kullanıldı. Empedans ve sertlik kontrol stratejileri modele bağlı yöntemler olduğu için test düzeneklerinin dinamik parametreleri adaptif gerçek zamanlı parametre tanımlama yöntemleri ile çevrim-içi tespit edildi. Sonuç olarak, empedans kontrol stratejisi kullanılarak dinamik karakteristiği değişkenlik gösterebilen, örneğin araç hızına bağlı olarak davranışı değişebilen bir direksiyon sistemi elde edilmiş oldu. Bu, araç kararlılığını iyileştirebilecek bir yöntem olarak tespit edildi.

COMPLIANT CONTROL OF ELECTRIC POWER ASSISTED STEERING SYSTEMS IN VEHICLES Vehicle directional control and driver interaction assemblies have been built to study and implement compliance control strategies on steer-by-wire systems. A nonlinear 4 DOF vehicle model, including the longitudinal, lateral, and yaw motions was derived using Newtonian mechanics to simulate and test the controllers. The fourth degree of freedom was the roll dynamics which was considered quasi-static to calculate the vertical load transfer between the tires during cornering, superposing the load transfer due to pitching of the vehicle body. Dugoff tire model was used to calculate the tire forces arising from tire-road interaction. Compliance control strategies were used to control the dynamic characteristics and return-to-center characteristics of the steering system. As compliance control strategies are model based, adaptive on-line estimation methods were used to identify the dynamic parameters of vehicle directional control and driver interaction assemblies. It was concluded that impedance and stiffness control strategies are suitable for steering systems.
Keywords: Otomotiv Sektörü; Otomotiv Sektörü_Güvenlik